Comparative analysis of reproductive tract microbiomes in modern and slower-growing broiler breeder lines - Shterzer, Naama; Sbehat, Yara; Poudel, Binita; Rothschild, Nir; Oloko, Olanrewaju Eunice; Druyan, Shelly; Mills, Erez (Frontiers in Veterinary Science, 2024)
The reproductive tract microbiome in hens is of interest because bacteria in the reproductive tract could potentially affect fertilization and egg production, as well as integrate into the forming egg and vertically transmit to progeny. Here, the reproductive tract microbiome of 37-week-old modern commercial Cobb breeding dams was compared with that of dams from a broiler Legacy line which has not undergone selection since 1986. All animals were kept together under the same management protocol from day of hatch to avoid confounders. In regards to reproductive abilities, Cobb dams’ eggs weighed more and the magnum section of their reproductive tract was longer. In regards to microbiome composition, it was found that the reproductive tract microbiomes of the two lines had a lot in common but also that the two breeds have unique reproductive tract microbiomes. Specifically, the order Pseudomonadales was higher in the magnum of Legacy dams, while Verrucomicrobiales was lower. In the infundibulum, Lactobacillales were higher in the Legacy dams while Verrucomicrobiales, Bacteroidales, RF32 and YS2 were lower. To conclude, our results show that breeding programs have modified not only the physiology of the reproductive tract but also the reproductive tract microbiome. Additional research is required to understand the implications of these changes in the reproductive tract microbiome on the chicken host.